2020
DOI: 10.1186/s12911-020-01247-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability, price, and affordability of WHO priority maternal and child health medicine in public health facilities of Dessie, north-East Ethiopia

Abstract: Background Access to health care is a fundamental human right, and the provision of affordable, high-quality, and appropriate medicines for maternal and child health is a vital component of a well-functioning health system. The study assessed the availability, price, and affordability of WHO priority maternal and child medicines in public health facilities, Dessie, North-East Ethiopia. Methods A retrospective cross-sectional study design was conducted in Dessie town from November 2018 to February 2019. A sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Eventually, a total of 18 studies were enrolled in this systematic review (Figure 1). The 18 included studies were all multicenter cross-sectional surveys and were conducted from 2009 to 2019 (Balasubramaniam et al, 2011;Anson et al, 2012;Ravindran et al, 2012;Balasubramaniam et al, 2014;Nsabagasani et al, 2015;Swain et al, 2015;Sado and Sufa, 2016;Xiao et al, 2017;Abrha et al, 2018;Gereltuya et al, 2018;Saisai et al, 2018; Sun et al, 2018;Guoxu et al, 2019;Neha et al, 2019;Orubu et al, 2019;Demerew and Ahmed, 2020;Xiao et al, 2020;Yi et al, 2020). All studies were conducted in low-income and middleincome countries, including China (6/18), India…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, a total of 18 studies were enrolled in this systematic review (Figure 1). The 18 included studies were all multicenter cross-sectional surveys and were conducted from 2009 to 2019 (Balasubramaniam et al, 2011;Anson et al, 2012;Ravindran et al, 2012;Balasubramaniam et al, 2014;Nsabagasani et al, 2015;Swain et al, 2015;Sado and Sufa, 2016;Xiao et al, 2017;Abrha et al, 2018;Gereltuya et al, 2018;Saisai et al, 2018; Sun et al, 2018;Guoxu et al, 2019;Neha et al, 2019;Orubu et al, 2019;Demerew and Ahmed, 2020;Xiao et al, 2020;Yi et al, 2020). All studies were conducted in low-income and middleincome countries, including China (6/18), India…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The IRP of medicines comes from the Guidelines for International Medicine Price Indicator Guide issued by the Management Sciences for Health (MSH) and is updated regularly. If the retail price of medicines in the public sectors does not exceed 1.5 times the IRP, MPR <1.5, or the retail price of medicines in the private sectors does not exceed 2 times IRP, MPR <2, the prices are considered reasonable (Abrha et al, 2018;Sun et al, 2018;Demerew and Ahmed, 2020;Xiao et al, 2020;Yi et al, 2020).…”
Section: Prices Of Medicines For Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven other supplementary medicines were chosen to treat important national health problems and the burden of local diseases for children (such as pneumonia, diarrhoea, colds and pain). When developing the supplementary list, we referenced medicine lists from previous studies, [9][10][11][12][13][14][15][16][17][18][19][20] guidelines and documents (such as the NEML (2018), 23 the seventh WHO EMLc (2019), 24 the WHO's list of priority life-saving medicines for women and children (2012) 25 . The suitability of selected medicines was also checked through the results from a pilot test in a public health facility and a private drugstore in October 2020.…”
Section: Surveyed Medicinesmentioning
confidence: 99%
“…There are only few studies on EMs for children (cEMs). [9][10][11][12][13][14][15][16][17][18][19][20][21] Their results showed that low availability, high prices and poor affordability have kept cEMs out of reach.…”
Section: Introductionmentioning
confidence: 99%